The analysis of the electric field and the dispersion relationship of a folded waveguide traveling wave tube using the Fourier transform - Fareq, Malek, Dr. (Universiti Malaysia Perlis (UniMAP), 2010)
1st Regional Conference on Applied and Engineering Mathematics (RCAEM-I) 2010 organized by Universiti Malaysia Perlis (UniMAP) and co-organized by Universiti Sains Malaysia (USM) & Universiti Kebangsaan Malaysia (UKM), 2nd - 3rd June 2010 at Eastern & Oriental Hotel, Penang.